Proprotein Convertases and the Complement System - Dobó, József; Kocsis, Andrea; Dani, Ráhel; Gál, Péter (Frontiers in Immunology, 2022)
Proteins destined for secretion - after removal of the signal sequence - often undergo further proteolytic processing by proprotein convertases (PCs). Prohormones are typically processed in the regulated secretory pathway, while most plasma proteins travel though the constitutive pathway. The complement system is a major proteolytic cascade in the blood, serving as a first line of defense against microbes and also contributing to the immune homeostasis. Several complement components, namely C3, C4, C5 and factor I (FI), are multi-chain proteins that are apparently processed by PCs intracellularly. Cleavage occurs at consecutive basic residues and probably also involves the action of carboxypeptidases. The most likely candidate for the intracellular processing of complement proteins is furin, however, because of the overlapping specificities of basic amino acid residue-specific proprotein convertases, other PCs might be involved. To our surprise, we have recently discovered that processing of another complement protein, mannan-binding lectin-associated serine protease-3 (MASP-3) occurs in the blood by PCSK6 (PACE4). A similar mechanism had been described for the membrane protease corin, which is also activated extracellularly by PCSK6. In this review we intend to point out that the proper functioning of the complement system intimately depends on the action of proprotein convertases. In addition to the non-enzymatic components (C3, C4, C5), two constitutively active complement proteases are directly activated by PCs either intracellularly (FI), or extracellularly (MASP-3), moreover indirectly, through the constitutive activation of pro-factor D by MASP-3, the activity of the alternative pathway also depends on a PC present in the blood.